Superior vena cava syndrome as a result of thrombosis in a child with nephrotic syndrome - Çalışkan, Salim; Sever, Lale; Sarıoğlu, Ayşe; Sarıoğlu, Tayyar; Kasapçopur, Özgür; Arısoy, Nil (The Turkish Journal of Pediatrics, 1997)
A three-year-old nephrotic girl is presented with vena cava superior syndrome. Angiography showed obliteration of the distal ends of both axillary veins and echocardiographic examination revealed a mobile mass in the right atrium. A thrombus originating from the vena cava superior with a stalk extending to the right atrium was surgically removed. To our knowledge, vena cava superior thrombosis in nephrotic syndrome has not been reported previously.
Keywords: nephrotic syndrome; vena cava superior; thrombosis; thromboembolic complication